THE CORRELATION OF MULTIPLE INTELLIGENCES AND ACADEMIC ACHIEVEMENT OF THE 2nd SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT, GANESHA UNIVERSITY OF EDUCATION - ., I Gede Wahyudi; ., Prof. Dr. Anak Agung Istri Ngr. Marha; ., A.A. Gede Yudha Paramartha, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Tujuan dari penelitian ini adalah untuk menginvestigasi 1) hubungan antara kecerdasan majemuk dengan prestasi akademik siswa dan 2) kecerdasan majemuk yang paling dapat memprediksi prestasi akademik siswa. Desain dari penelitian ini menggunakan ex post facto dengan analisis korelasi. Sampel dalam penelitian ini berjumlah162 siswa yang dipilih secara acak dari siswa semester 2 Pendidikan Bahasa Inggris, Universitas Pendidikan Ganesha. Multiple Intelligences kuisoner yang diadopsi dari McKenzie (1999) dan Armstrong (2009) digunakan untuk memperoleh data dari kecerdasan majemuk siswa, sementara itu nilai prestasi akademik siswa diperoleh melalui KHS. Uji korelasi Spearman’s rho digunakan untuk mengetahui hubungan antara kecerdasan majemuk dengan prestasi akademik siswa. Hasilnya menunjukan bahwa kecerdasan verbal-linguistic, musical, visual-spatial, bodily-kinesthetic, intrapersonal, interpersonal, naturalistic, dan existential mempunyai hubungan yang positive dengan prestasi akademik siswa. Sementara itu, kecerdasan logical-mathematical tidak mempunyai hubungan dengan prestasi akademik siswa. Lebih lanjut lagi, secara berurutan, kecerdasan yang paling bisa memprediiksi prestasi akademik siswa. adalah (1) verbal-linguistic, (2) existential dan (3) intrapersonal.Kata Kunci : kecerdasan majemuk, prestasi akademik The purpose of this study is to investigate (1) the correlation among multiple intelligences and students’ academic achievement and (2) the most predictive intelligences of academic achievement. The design of this study was ex-post facto with a correlational analysis. Sample was 162 students randomly selected from the second semester of English Education Department, Ganesha University of Education. The Multiple Intelligences Questionnaire adopted from McKenzie (1999) and Armstrong (2009) was used to collect the data of the students’ multiple intelligences, while the data of academic achievement was collected through GPA document. Spearman’ rho correlation was used to investigate the correlation among multiple intelligences and students’ academic achievement. The results indicate that verbal-linguistic, musical, visual-spatial, bodily-kinaesthetic, intrapersonal, interpersonal, naturalistic, and existential intelligence have positive and significant correlation with students’ academic achievement. Whereas, logical-mathematical intelligence has no significant correlation to academic achievement. Moreover, the most predictive intelligences to academic achievement are subsequently, (1) verbal-linguistic, (2) existential and (3) intrapersonal intelligence keyword : academic achievement, multiple intelligences